If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5v+1-3(-2v-1)=2(v-4)
We move all terms to the left:
5v+1-3(-2v-1)-(2(v-4))=0
We multiply parentheses
5v+6v-(2(v-4))+3+1=0
We calculate terms in parentheses: -(2(v-4)), so:We add all the numbers together, and all the variables
2(v-4)
We multiply parentheses
2v-8
Back to the equation:
-(2v-8)
11v-(2v-8)+4=0
We get rid of parentheses
11v-2v+8+4=0
We add all the numbers together, and all the variables
9v+12=0
We move all terms containing v to the left, all other terms to the right
9v=-12
v=-12/9
v=-1+1/3
| 6-1x=8.25-1x | | -7=1.97+h | | 14x-6=4x+34 | | 9(n-4)=56 | | 1.7(f+1.4)=9.35 | | 1x/7-4/3=-1/2 | | -1/3(9z+42)-5z=-70 | | 3y–15=(–21) | | .18=5a-2a+3 | | t-7=83 | | 10x-12=6x-610x−12=6x−6 | | 6x-50=1x+70 | | 274=63-y | | -8r-3=-1r | | 17x-19=60 | | 11+150=-8(-3w-3)-7 | | 3p+6=-(1+4p) | | 2+4r-10+6r=2(5r-4) | | -5x-20=50 | | 32+9x+1=13x-11 | | -7y+5=-6y+11 | | 5x+35=7x+15 | | 2x-12+2x+17+9x-7=180 | | 8x=(3x+5)+(6x-16) | | 7/3=x/1.5 | | (4x-13)=(3x+19)= | | x+x2=x(x+1) | | 3y–15=–21 | | 2x^2+3x=374 | | 15h-9=-4 | | 5(r-1)=2(r-4)=6 | | 4(3+6x)=10(4x-2) |